2010
DOI: 10.1590/s0101-28002010000100017
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação das pressões respiratórias máximas em pacientes renais crônicos nos momentos pré e pós-hemodiálise

Abstract: Introduction and Objective: Maximal inspiratory and expiratory pressures (PI max and PE max ) are used to assess the integrity of respiratory muscles by measuring their strength. The aim of this study was to assess the immediate influence of hemodialysis (HD) on respiratory muscle strength by measuring PI max and PE max , investigating the integrity of that musculature and/or the presence of muscular weakness. Method: A prospective, crosssectional study was carried out on a convenience sample of 35 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
9

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 26 publications
1
10
0
9
Order By: Relevance
“…Parreira et al (2007) 25 , assessing the maximal respiratory pressures of healthy patients, have reported that measurements are influenced by the understanding about the maneuvers to be performed and by the will of the participants to cooperate and perform really maximum respiratory movements and efforts. That is in accordance with the study by Rocha et al (2010) 16 , who have discussed measurement as depending on the understanding and collaboration of the participants, and have concluded that learning the technique has a determinant effect, either positive or negative, on the results obtained. Those aspects can be considered as qualitatively influencing the results of the present study.…”
Section: Discussion Respiratory Variablessupporting
confidence: 91%
See 3 more Smart Citations
“…Parreira et al (2007) 25 , assessing the maximal respiratory pressures of healthy patients, have reported that measurements are influenced by the understanding about the maneuvers to be performed and by the will of the participants to cooperate and perform really maximum respiratory movements and efforts. That is in accordance with the study by Rocha et al (2010) 16 , who have discussed measurement as depending on the understanding and collaboration of the participants, and have concluded that learning the technique has a determinant effect, either positive or negative, on the results obtained. Those aspects can be considered as qualitatively influencing the results of the present study.…”
Section: Discussion Respiratory Variablessupporting
confidence: 91%
“…12 Alterations in the respiratory muscle function, pulmonary mechanics, and gas exchanges are frequent in patients with CKD . 6 Several studies have shown that such patients undergoing HD have a reduction in the respiratory muscle strength 3,6,7,14,[16][17][18]20 and pulmonary function. 3,13,14,18,20 On reassessment, the MIP and MEP values showed no statistically significant changes, which may have been due to lack of specific training to strengthen respiratory muscles.…”
Section: Discussion Respiratory Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…Este resultado corrobora o estudo realizado por Rocha e Araújo (2010), 30 mostrando redução dos valores da PImax e PEmax em relação aos valores preditos nos momentos pré e pós-intervenção. Porém, relacionando os momentos pré e pós-programa de exercícios, apenas a PImax apresentou aumento.…”
Section: Variáveisunclassified